ANALISIS MAKNA KATA KAKERU (KAJIAN LINGUISTIK KOGNITIF) - Chintia Sari Piranawati (STBA LIA - Jakarta, 2022)
The existence of polysemy in Japanese can be one of the factors causing difficulties in learning Japanese. In addition, polysemy may make Japanese language learners misunderstand the meaning of a word in a sentence which causes errors to occur either when learning Japanese or when communicating with other people using Japanese. The purpose of this study is to describe the polysemy of the word kakeru in Japanese using a study of cognitive linguistics. This study uses a qualitative descriptive research method. Data sources consist of Nihongo Daijiten (Tadao, 1995), Kokugo Jiten (Matsumura, 2005), and the Japanese-Indonesian Dictionary (Matsuura, 1994), and online media portals (Jakarta shinbun, Asahi shinbun, Yomiuri shinbun, and corpus data from Ninjal-LWP). The results of this study found that the basic meaning of the verb kakeru is menggantung with 13 expansion meanings consisting of menaruh, menimbang, menuangkan, membungkus, meningkatkan, memercayakan, mengamankan, and rentang/jarak which has the form of metaphorical style, then there’re membayar, mengalikan, and menghabiskan for the form of metonymy style, and the last one is rentang/jarak for the form of synecdoche style.